Bringing nexus thinking to the UN 2023 Water Conference - Smith, Mark (CGIAR System Organization, 2023)
On Wednesday, March 22, thousands of delegates from around the world will arrive in New York for the United Nations (UN) 2023 Water Conference. The first global freshwater conference in almost 50 years, this three-day event marks a unique opportunity to ensure that systems thinking is at the heart of national and international responses to the world’s mounting water challenges.